ax^2+bx+c=0
a(x^2+b/a*x+c/a)=0(提取公因式a)
a[x^2+b/a*x+(b/2a)^2-(b/2a)^2+c/a]=o(凑完全平方公式)
a[(x+b/2a)^2-b^2/4a^2+c/a]=o(合并完全平方式)
a(x+b/2a)^2-b^2/4a^2+c=0(去括号)
a(x+b/2a)^2=b^2/4a-c(移项)
(x+b/2a)^2=b^2/4a^2-c/a(左右同乘a)
x+b/2a=±√(b^2/4a^2-4c^2/4a^2)(左右开根号)
x+b/2a=±√[(b^2-4ac)/4a^2](通分)
x=[-b±√(b^2-4ac)]/2a(移项、通分)
∴在ax^2+bx+c=0中,x=[-b±√(b^2-4ac)]/2aax^2+bx+c=0
a(x^2+b/a*x+c/a)=0(提取公因式a)
a[x^2+b/a*x+(b/2a)^2-(b/2a)^2+c/a]=o(凑完全平方公式)
a[(x+b/2a)^2-b^2/4a^2+c/a]=o(合并完全平方式)
a(x+b/2a)^2-b^2/4a^2+c=0(去括号)
a(x+b/2a)^2=b^2/4a-c(移项)
(x+b/2a)^2=b^2/4a^2-c/a(左右同乘a)
x+b/2a=±√(b^2/4a^2-4c^2/4a^2)(左右开根号)
x+b/2a=±√[(b^2-4ac)/4a^2](通分)
x=[-b±√(b^2-4ac)]/2a(移项、通分)
∴在ax^2+bx+c=0中,x=[-b±√(b^2-4ac)]/2aax^2+bx+c=0
a(x^2+b/a*x+c/a)=0(提取公因式a)
a[x^2+b/a*x+(b/2a)^2-(b/2a)^2+c/a]=o(凑完全平方公式)
a[(x+b/2a)^2-b^2/4a^2+c/a]=o(合并完全平方式)
a(x+b/2a)^2-b^2/4a^2+c=0(去括号)
a(x+b/2a)^2=b^2/4a-c(移项)
(x+b/2a)^2=b^2/4a^2-c/a(左右同乘a)
x+b/2a=±√(b^2/4a^2-4c^2/4a^2)(左右开根号)
x+b/2a=±√[(b^2-4ac)/4a^2](通分)
x=[-b±√(b^2-4ac)]/2a(移项、通分)
∴在ax^2+bx+c=0中,x=[-b±√(b^2-4ac)]/2a